Analisis Pengendalian Defect dengan Menggunakan Metode Six Sigma (DMAIC) pada Produksi Glass Block di PT XYZ - Mufamar Ivan; Setiawan Setiawan; Hasyrani Windyatri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT XYZ is a manufacturing company that produces glass blocks and continues to face quality-related issues, particularly a high number of defects caused by mold disturbances during the production process. The high defect rate indicates that the production process is still subject to significant variation, highlighting the need for a structured quality control system. This study aims to evaluate the process capability of the production system, analyze the defect rate caused by mold disturbances, and implement defect control using the Six Sigma methodology with the DMAIC (Define, Measure, Analyze, Improve, and Control) approach. The results show that the average sigma level of the production process was 3.67, indicating that the primary causes of defects were related to machine, method, and human factors. Based on the analysis, the proposed improvements focused on implementing periodic preventive maintenance for molds, developing a mold inspection checklist, enhancing mold condition monitoring, and providing operator training. The evaluation conducted after the improvement phase demonstrated that the number of defects decreased from 17,027 to 6,693, while the sigma level increased from 3.67 to 4.00, indicating improved process stability and enhanced glass block production quality.